NEGOTIATING POWER AND IDENTITY THROUGH CONVERSATIONAL IMPLICATURES: CROSS-CULTURAL COMMUNICATION OF THE MAIN CHARACTERS IN PURPLE HEARTS MOVIE - Ayiz, Abdul; Carreon, Jonathan Rante; Marginingsih; Yanottama, Fourica (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
In everyday communication, speakers often rely on indirect expressions whose meanings must be inferred from context, making conversational implicatures a key element in understanding how language functions beyond its literal form. This study investigates how conversational implicatures function as tools for negotiating power and identity in cross-cultural communication, as portrayed by the main characters in Elizabeth Allen Rosenbaum’s Purple Hearts (2022). Guided by a sociopragmatics perspective, the research examines how implicit meanings in dialogue both reflect and shape interpersonal dynamics between Cassandra Salazar, a liberal musician, and Luke Morrow, a conservative U.S. Marine. The study employed a descriptive qualitative method with an ethnographic approach, analyzing 56 utterances drawn from the film’s subtitles. Findings reveal that particularized conversational implicatures (PCI) are the most dominant type, followed by generalized conversational implicatures (GCI) and scalar implicatures (SI). These implicatures serve not only to convey hidden meanings but also to express sarcasm, resistance, politeness, vulnerability, and emotional tension. The results demonstrate that implicatures are central to power relations, with Luke often using them to subtly assert institutional authority, while Cassandra employs them as acts of resistance and identity assertion. Over time, their communication shifts from conflict to adaptation, showing how cultural differences—liberal versus conservative worldviews, expressive versus restrained styles—both complicate and enrich cross-cultural interactions. This study contributes to sociopragmatics research by highlighting how cinematic discourse embodies ideological conflicts and identity negotiation, and how conversational implicatures facilitate cultural convergence in cross-cultural relationships.